Tradition und Moderne in Bewegung - Ozil, Seyda; Hofmann, Michael; Laut, Jens-Peter; Dayioglu-Yücel, Yasemin; Zierau, Cornelia; Uca, Didem (Universitätsverlag Göttingen, 2018)
The articles in this volume bear witness to the productive energy of the interplay between tradition and modernity, whether in theater, literature, or popular culture. At the same time, they emphasize the importance of cultural intermediaries, including translators. The volume thus illustrates that - despite (or precisely because of) political developments in Turkey and Germany, alike - a multitude of Turkish-German themes remain vital in both society and the academy, urging further consideration, investigation, discussion, and presentation.